Pengaruh Laba Akuntansi terhadap Return Saham: (Studi Empiris pada Emiten Sub Sektor Food and Beverage) - Amelia Destiyana; Sumarno Manrejo; Bambang Prayogo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine whether there is an effect of accounting profit on stock returns of food and beverage issuers listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample selection in this study used purposive sampling with the specified criteria, obtained 14 companies for 5 periods so that the total sample used was 67 data. The data analysis used in this study is quantitative, using the SPSS version 25 tool. The results of this study are that partially accounting profit positive affect stock return.